PROFILOPLASTY: STRATEGIC FILLINGS IN THE MIDDLE AND LOWER THIRD OF THE FACE - Helena Martins Félix, Laryssa; Cristina Maurício Milagre Diniz, Helen (Health and Society, 2022)
Profileplasty encompasses the study of facial proportions and the treatment of profile disharmonies to achieve a more balanced aesthetic. One of the forms of treatment is the evaluation of facial thirds and angles, and consequently the use of injectable fillers as an option to achieve the beauty standards defined by this science. In this work, a facial analysis was performed using measurements of angles and facial thirds, documented by photographs. Through these results, injectable fillers with Hyaluronic Acid were made at strategic points in order to improve measurements and directing the patient to the beauty standards defined by profiloplasty.